Is competition just a question of numbers? An analysis of the impact of the entry of Free Mobile into the French mobile telecommunications market - Michel Berne; Pierre Vialle; Jason Whalley (International Telecommunications Society (ITS), 2016)
In recent years across Europe, mobile operators have made a number of attempts to consolidate. Consolidation, whether it is successful or not, inevitably focuses on the number of mobile network operators present in a market. Largely overlooked in the discussion of how many mobile network operators should be permitted in a market is the strategy(s) adopted by these operators. An operator may have a disruptive impact on the market, necessitated by its late entrance, that takes the form of price, handset or bundling based competition. In this paper we explore the impact that one such disruptive mobile operator, Free Mobile, has had on the French mobile telecommunications market. Drawing on a wide range of secondary sources, our analysis finds that the growth of Free has come at the expense of the incumbent mobile operators. Its innovative approach to selling its products and providing customer support have been copied by its rivals, as has its low cost strategy. While consolidation has often been rumoured, it has not occurred with the consequence that Bouygues Telecom finds itself in a particularly precarious situation as it is squeezed between larger rivals like Orange and price focused competitors like Free Mobile.
Keywords: 330; competition; mobile telecommunications; Free Mobile; France; entry